Tall tower observations of a northward surging gust front in central Amazon and its role in the mesoscale transport of carbon dioxide - Luciane I. Reis; Maurício I. Oliveira; Cléo Q. Dias‐Júnior; Hella vanAsperen; Luca Mortarini; Otávio C. Acevedo; Christopher Pöhlker; Leslie A. Kremper; Bruno Takeshi; Carlos A. Quesada; Daiane V. Brondani (Meteorological Applications, 2024)
Abstract High‐frequency measurements obtained at two micrometeorological towers are investigated for a rare northward surging gust front that impacted the Amazon Tall Tower Observatory (ATTO), in central Amazon. The gust front originated from a decaying mesoscale convective system (MCS) during the morning hours of 27 December 2021 near Manaus, Amazonas state, northern Brazil, and surged north‐eastward towards the ATTO site. Large temperature drops and vigorous, persistent winds were observed at the towers which lasted for over 4 h despite the gust front being detached from its parent, decaying MCS. More importantly, the gust front was responsible for drastic increases of CO2 concentrations throughout the tower depths, which suggests that the gust front winds horizontally advected CO2‐rich air from a source upstream from the ATTO site. The CO2‐rich outflow is hypothesized to originate from downward transport and/or biomass burning from forest fires in southeastern Amazon, both ideas that are supported by large increases of aerosol concentrations measured at ATTO following the gust front passage. Our results stress the need for further investigations addressing the role played by mesoscale convective circulations in the redistribution of trace gases and aerosols in the Amazon.